Improving streetscape element at Seksyen 14, Shah Alam City Centre / Afiq Syahmi Mokhlis - Afiq Syahmi, Mokhlis (2020)
The streetscape is function as the backbone and key element for encouraging the pedestrian usage toward healthy city. However, the poor design, lack of maintenance and not attractive especially at the city centre have lead to the community not using pedestrian area. The purpose of this study is to implement the streetscape element at Seksyen 14, Shah Alam city centre toward healthy city. This study is use the observation method in collecting the data by determining the number, existence, location and condition of the streetscape for future improvement. There are 11 streetscape elements have been study in this research including sidewalk, curb extension, bollard, landscape strip, seat, trach can, public art, lighting, planter box, pedestrian crossing and universal design. The research found there 11 streetscape elements in Shah Alam City Centre, Seksyen 14 can improve and implement the new streetscape elements to encouraging the use of pedestrian area toward healthy city. In conclusion the improvement and implementation of new streetscape in the Shah Alam City Centre can enhance the function of the pedestrian in way to healthy life style of community and solve the problem of poor streetscape elements in city centre.